Research on the Influence of Liquid Metal Embrittlement Cracks on the Strength and Fatigue Life of Spot-Welded Joints of Galvanized Q&P980 Steel - Zou, Jie; Xiang, Huayang; Zhan, Zhenfei; Zhuo, Wenbo; Huang, Li; Ji, Yuxiang; Liu, Qing (Materials, 2024)
Galvanized high-strength steel has emerged as a key focus in automotive lightweighting research. During resistance spot welding of galvanized steel, the phenomenon of liquid metal embrittlement (LME) can occur, which is characterized by the appearance of irregular cracks on the weld spot surface. However, the impact of LME cracks on the mechanical properties of joints remains unclear. This study investigates the LME phenomenon and its effects on the performance of spot-welded joints using galvanized QP980 steel as the subject. By combining theoretical analysis, experimental methods, and simulations, the formation and characteristics of LME cracks are explored through resistance spot welding experiments and elemental analysis. The influence of LME cracks on the static strength of joints is assessed through quasi-static tensile tests, fracture surface analysis, and theoretical calculations. Finite element simulations of the static tensile process reveal that LME cracks alter the stress–strain fields during joint failure. Additionally, the study examines how the location and size of LME cracks influence these effects. Finally, fatigue testing and fracture analysis of spot-welded joints demonstrate that LME cracks can negatively impact the fatigue life of joints.